Numerical and experimental investigation on mechanical and thermal behaviour of brick masonry: An efficient consumption of ultrafine fly ash. (30th August 2020) - Krishnaraj, L.; Niranjan, R.; Kumar, G. Prem; Kumar, Rajendran Senthil
Graphical abstract: Highlights: Environmental impacts can be reduced through utilization of fly ash and reduces the emission of CO2 The particles ball milled into ultrafine particles to increase specific surface area. Particle size reduction supports physical and strength aspects. Pulverizing aids improves the particle size reduction, grind ability with lesser energy. In addition to this the thermal properties of materials were analyzed. Also, the comparison is made between the Experimental and Numerical results. Abstract: The study aims to investigate the impact of Ultrafine Fly Ash (UFFA) blended cement mortar in masonry prism and its failure mechanisms. Class C fly ash (CFA) and UFFA with optimum pulverization time of 120 min and replacement of 50% in cement mortar was examined. Masonry prism made of clay and fly ash brick are exposed for compressive and shear loads to test the real field scenario. UFFA mortar has more specific heat capacity (Cp) due to existence of finer particles. In real time, heat transferring of wall, the brick plays a dominant role on volume basis which balances the enhancement of Cp of mortar efficiently. Interestingly, 50% replacement of UFFA guarantees the additional strength of 8% and 33% over the conventional mortar and masonry prism respectively, due to its size reduction, irregular shape and greater interlocking of hydrated products. Experimental results have been validated numerically using ANSIS workbench 18.